Appropriation of Scientific Writing by University Students: Challenges in a Vocational Guidance Program - Supeno, Eddy; Rioux, Isabelle; Bélisle, Rachel (Canadian Journal of Counselling and Psychotherapy, 2019)
The appropriation of scientific writing represents a challenge for academics, especially in graduate students’ training where the production of a dissertation or a thesis is mandatory in many programs. Although the cognitive dimension of this form of writing has been well documented, some studies underline its multidimensional character. Training programs in counseling, in particular, are characterized by disciplinary diversity where numerous epistemological positions may influence graduate students’ appropriation of scientific writing. Based on qualitative data collected with a focus group of master’s students in vocational guidance, a clinical training program involving several forms of writing, the results show that social/relational and affective dimensions also play a major role in the appropriation of scientific writing.